2011
DOI: 10.1093/humrep/der222
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of the glucocorticoid receptor may affect the phenotype of women with anovulatory polycystic ovary syndrome

Abstract: The present study did not identify risk alleles for PCOS, although the study was limited by an absence of endocrine data for the population-based controls. However, GCR variants may influence gonadotrophin levels in women with anovulatory PCOS. We hypothesize that glucocorticoids can affect the function of the hypothalomo-pituitary-gonadal axis in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…The H6PD SNP rs668832 has been examined extensively but has demonstrated a consistent lack of association with CRD/ACRD, hyperandrogenism, or PCOS (40,(42)(43)(44)58). Only 2 small case-control studies suggest that rs668832 is associated with PCOS (45,59).…”
Section: Genetic Variation In the H6pd Gene And Influence On 11␤-hsd1mentioning
confidence: 99%
“…The H6PD SNP rs668832 has been examined extensively but has demonstrated a consistent lack of association with CRD/ACRD, hyperandrogenism, or PCOS (40,(42)(43)(44)58). Only 2 small case-control studies suggest that rs668832 is associated with PCOS (45,59).…”
Section: Genetic Variation In the H6pd Gene And Influence On 11␤-hsd1mentioning
confidence: 99%
“…Despite PCOS prevalence and health implications, there is no gold standard for long-term treatment of women with PCOS and the etiology of PCOS remain unclear. Interestingly, it has also been demonstrated that PCOS is a multifactorial disease with polygenic nature, and this heterogeneity complicates the effort to investigate additional genetic components of its pathogenesis (3). The DENN domain containing 1a (DENND1A) gene, a member of a family of 18 human genes termed “connecdenns”, has gained recognition as a strong PCOS susceptibility gene in several studies (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, other studies (Ewens et al, 2010;Qin and Rosenfield, 2011;Valkenburg et al, 2011) have not replicated our published association between R453Q and PCOS , since the emerging picture of PCOS is that of a complex multigenic trait in which modifying environmental factors play an important role in the expression of the hyperandrogenic phenotype. Differences in these environmental factors, especially those pertaining to diet and life-style, could contribute to explain the discrepancies among our previous and present results and those of other studies conducted in women from the United States and Northern Europe (Ewens et al, 2010;Qin and Rosenfield, 2011;Valkenburg et al, 2011). Additionally, the pathogenesis of PCOS probably differs among the different phenotypes of the syndrome, as has been proposed by others (Gambineri et al, 2006).…”
Section: Discussionmentioning
confidence: 67%